PENANAMAN KARAKTER MELALUI PENDEKATAN SOSIOLOGI PENDIDIKAN PADA SISWA ASRAMA INSAN CENDIKIA BOARDING SCHOOL (ICBS) MIN 1 BANYUMAS - Muhammad Hafidza Daffa Nurdiansyah; Muh. Hanif (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
Character education in boarding school environments plays a crucial role in shaping students' morality and social identity. This study explores the implementation of character-building strategies based on an educational sociology approach among sixth-grade students at the Insan Cendikia Boarding School (ICBS) Dormitory of MIN 1 Banyumas. Using a qualitative case study method, data were collected through participant observation, in-depth interviews, and documentation. The results indicate that strategies such as habituation, role modeling, group norm reinforcement, communicative approaches, and local culture effectively instill values like discipline, responsibility, cooperation, empathy, and social care. The findings underscore the importance of integrating social dynamics and regional cultural values into character education, presenting an innovative approach to building students' moral foundations through sustainable collective experiences.